Simulation on the Application Minister Agriculture Republic of Indonesia No. 28 the Year 2020 and Its Impact on the PT Pupuk Kujang Performance - Fulki Fathurrahman; Muhammad Dahlan; Sofik Handoyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research was conducted on State-Owned Enterprises in Indonesia. This study aims to analyze the impact of the application of permentan RI number 28 of 2020 on the performance of PT Pupuk Kujang in terms of the company's profit, the company's financial ratio and the company's going concern using the altman Z-Score. Metode the research used is a mix method. The results showed that the implementation of Permentan no. 28 of 2020 has different significant on financial distress.  The benefit of this research is that PT Pupuk Kujang should be aware if the altman Z-Score value continues to decline so that whatisnot anticipated will bring the company into bankruptcy (Financial distress). This is due to the high sales of subsidized fertilizers as the main source of income.